(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article discusses the issues of sustainable tourism, the development of Gegharkunik Region, as well as the main problems undermining development. The introduction and application of the principles and ideas of sustainable tourism is extremely important in the development of tourism in the region․ Based on the problems hindering the development of sustainable tourism, it is possible to develop a sustainable strategic plan that will be in the interests of the socio-economic development of the region. Gegharkunik Region has unique natural conditions and opportunities for sustainable tourism development, however, the development of the tourism industry is not fully underway, since these resources and opportunities are not used or are partially used in the interests of tourism development. The tourist attraction and interest in these resources are also not fully represented. This article takes as a basis the approach according to which the principles of sustainable development should be taken into account in the development of sustainable tourism in Gegharkunik Region, those of active cooperation of stakeholders in the field, partnerships between the public and private sectors, international and regional cooperation and much more.